Keputusan Pembelian Berbelanja Di E-Commerce Pada Masyarakat Kelas Bawah Di Jakarta - Mutia Aisyatur Ridho; Dwi Sukanti Lestariningsih; Ode Sofyan Hardi (Journal of Social Science Education, 2021)
This study aims to determine the purchasing and shopping decisions in e-commerce in the lower class society in Jakarta which is reflected in the aspects of space, time, internal and external. This study uses a descriptive method with a survey approach. The basis for classifying the lower social class is seen from the Index Of Social Position (ISP) taken in RW Kumuh. The population in this study were the lower social class in RW 08 Kel. Pejaten Barat. Samples were taken as many as 30 respondents. The results showed that in the spatial aspect, lower class people often buy fashion products in online stores with e-commerce. Fashion is what most people buy in Jabodetabek. This is because the price is cheaper when buying it at online stores and there are many promos and the most purchased products outside Jabodetabek are fashion products. In terms of time, the average shopping at online stores is less than 3 times a month. On the internal aspect, the purpose of choosing to shop on e-commerce is because the price is cheaper. E-commerce shopping places that are frequently visited are Lazada and shopee and the payment method that is often used is COD or pay on the spot. the average cost of spending on E-commerce in a month is Rp. 100,000 - 500,000. On the external aspect, the form of promotion that can influence shopping in e-commerce is advertising.